Islamic Law on Peace Agreements in Murabahah Dispute Resolution: An Analysis in Banyumas Religious Court - Nada, Syifaun (Interdisciplinary Journal of Social Science and Education (IJSSE), 2024)
This study aims to determine the basis of the nature of the peace deed in the settlement of murabahah disputes in the Banyumas Religious Court. The main problem to be revealed in this study is how the review of Islamic engagement law on the peace deed in the settlement of murabahah disputes in the Banyumas Religious Court. The research method used by the author is included in literature law research. This literature research focuses on the scope of legal conception, legal rules, and legal principles, not up to human behavior. The results of this study show that the Parties to the peace deed have indirectly applied some of the provisions of the engagement based on the Islamic law of engagement, both from the provisions of the principle or principle, the provisions of the pillars, and the provisions of the terms and some things are not applied under these provisions. So, the law of the peace deed is binding and can be implemented as the provisions of Islamic law by both parties. This means that the Banyumas Religious Court has implemented the positive rule of law well, but on the other hand has implemented the legal provisions that apply to Islam. This peace deed becomes the basic agreement document of the parties to execute or execute the agreement that has been decided by the judge. Thus, the parties must abide by it in order for the benefit of this agreement to be achieved.